An Experience Report About Challenges of Software Engineering as a Second Cycle Course - Leite, Felipe Torres; Coutinho, Jarbele C. S.; Sousa, Reudismam Rolim de (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2020: Anais do XXXIV Simpósio Brasileiro de Engenharia de Software, 2020)
The dynamism of the software development market has demanded increasingly qualified professionals with practical knowledge on the implementation of paradigms and methodologies in the development of projects. In this context, there are undergraduate courses in Software Engineering (SE) offered in the format of two cycles, to try to deliver to the market professionals who meet the demands of the sector. Therefore, it is important to know the challenges that arise in the teaching scenario and the emerging topics of SE, in order to provide students with an academic-professional training closer to the real scenario of the software industry. Thus, this article aims to identify the difficulties observed in an undergraduate course in SE and its emerging topics, in the form of two cycles. For this, a survey with professors from a two-cycle SE course was carried out. Through a quantitative and qualitative analysis of the results, it was possible to identify some main challenges faced by professors. This type of analysis has proved to be useful to identify opportunities for improvement in the academic-professional training of SE students and to provide the software industry with more qualified professionals.